The rising threat of Nipah virus: a highly contagious and deadly zoonotic pathogen - Arindam Ganguly; Saptarshi Mahapatra; Shibsankar Ray; Sayantan Chattopadhyay; Md. Jabiul Islam; Sathi Garai; Tapas Kumar Dutta; Manasi Chattaraj; Sourav Chattaraj (Virology Journal)
Abstract The Nipah virus (NiV) is a highly virulent zoonotic infectious agent that poses a significant threat to public health. The virus is characterized by its pleomorphic structure and a single-stranded negative-sense RNA genome. It encodes six structural proteins and three nonstructural proteins. Attachment glycoproteins play a crucial role in allowing the virus to attach to the host cell surface. The matrix protein facilitates the encapsidation of the viral genome and proteins, enabling the formation of mature viral particles. The virus can spread via different routes, including zoonotic spillover and human-to-human transmission. Clinical manifestations include mild respiratory illness and severe and fatal encephalitis. The case fatality rate of Nipah virus infection varies widely, ranging from 40 to 75%, and is regulated by factors such as healthcare availability and quality, the patient's condition, and the virulence of the infecting strain. NiV has been reported in Malaysia, Bangladesh, and India, with fruit bats serving as natural reservoirs. Early detection and prompt response are crucial for controlling outbreaks; however, these efforts are hindered by diagnostic challenges and delayed recognition. The World Health Organization has categorized NiV as a priority pathogen owing to its epidemic potential, recurrent outbreaks, and alarming mortality rates. The persistent transmission dynamics and genetic stability of the Nipah virus among fruit bats require immediate attention and coordinated global action. The present study reviews the epidemiology, clinical features, and modes of transmission of Nipah virus infection, its geographical distribution, and endemic regions, highlighting the challenges in managing disease outbreaks.